Challenges of Convalescent Plasma Infusion Therapy in Middle East Respiratory Coronavirus Infection: A Single Centre Experience. Issue 7 (October 2018) - Ko, Jae-Hoon; Seok, Hyeri; Cho, Sun Young; Ha, Young Eun; Baek, Jin Yang; Kim, So Hyun; Kim, Yae-Jean; Park, Jin Kyeong; Chung, Chi Ryang; Kang, Eun-Suk; Cho, Duck; Müller, Marcel A; et al.
Background: The effects of convalescent plasma (CP) infusion, one of the treatment options for severe Middle East respiratory syndrome coronavirus (MERS-CoV) infections, have not yet been evaluated. Methods: Serological responses of CP-infused MERS patients during the 2015 Korean MERS outbreak at a tertiary care centre were evaluated. Serological activity was evaluated with anti-MERS-CoV enzyme-linked immunosorbent assay (ELISA) immunoglobulin (Ig)G, ELISA IgA, immunofluorescence assay IgM and plaque reduction neutralization test (PRNT). Donor plasma and one or two recipient's serum samples per week of illness including one taken the day after each CP infusion were evaluated. For sensitivity and specificity analysis of ELISA IgG in predicting neutralization activity, a data set of 138 previously evaluated MERS-CoV-infected patients was used. Results: Three of thirteen MERS patients with respiratory failure received four CP infusions from convalesced MERS-CoV-infected patients, and only two of them showed neutralizing activity. Donor plasma with a PRNT titre 1:80 demonstrated meaningful serological response after CP infusion, while that with a PRNT titre 1:40 did not. ELISA IgG predicted neutralization activity of a PRNT titre ≥1:80 with more than 95% specificity at a cutoff optical density (OD) ratio of 1.6, and with 100% specificity at an OD ratio of 1.9. Conclusions: For effective CP infusion in MERS, donor plasma with a neutralization activity of a PRNT titre ≥1:80 should be used. ELISA IgG could substitute for the neutralization test in resource-limited situations.